2011
DOI: 10.1016/j.wocn.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic conditioning of phonetic detail in German plosives

Abstract: a b s t r a c tThis study investigates the prosodic conditioning of phonetic details which are candidate cues to phonological contrasts. German /b, d, g, p, t, k/ were examined in three prosodic positions. Lenis plosives /b, d, g/ were produced with less glottal vibration at larger prosodic boundaries, whereas their VOT showed no effect of prosody. VOT of fortis plosives /p, t, k/ decreased at larger boundaries, as did their burst intensity maximum. Vowels (when measured from consonantal release) following for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…To summarize, the palatal and the velar show strong lengthening effects on stop burst duration under lexical stress, a result which is in line with previous results for many Germanic languages (see Kuzla & Ernestus, 2011 for a review). By contrast, the bilabial shows a smaller lengthening effect, and most importantly, the neutralized but stressed apical /T/ does not show any lengthening effect at all in comparison to Word-medial unstressed /t/ and /ʈ/ bursts.…”
Section: The Question Of Burst Durationsupporting
confidence: 91%
See 1 more Smart Citation
“…To summarize, the palatal and the velar show strong lengthening effects on stop burst duration under lexical stress, a result which is in line with previous results for many Germanic languages (see Kuzla & Ernestus, 2011 for a review). By contrast, the bilabial shows a smaller lengthening effect, and most importantly, the neutralized but stressed apical /T/ does not show any lengthening effect at all in comparison to Word-medial unstressed /t/ and /ʈ/ bursts.…”
Section: The Question Of Burst Durationsupporting
confidence: 91%
“…Fougeron & Keating, 1997;Tabain, 2003b;Cho, 2006-see Cho, 2011 for further references), although some work has looked at the acoustic, and subsequently perceptual, consequences of these segmental prosodic effects (e.g. Cho, McQueen, & Cox, 2007;Kuzla & Ernestus, 2011;Tabain, 2003a). A particular focus has been on the differences between effects caused by lexical stress, effects caused by contrastive focus, and effects caused by place in the prosodic hierarchy (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has focused on the articulatory consequences of prosodic structure, both on consonants and on vowels (e.g., Beckman & Edwards, 1994;Cho, 2005;Cho & Keating, 2009;de Jong, 1995;Fougeron & Keating, 1997;Tabain, 2003b;see Cho, 2011, for further references), although some work has looked at the acoustic, and subsequently perceptual, consequences of these segmental prosodic effects (e.g., Cho et al, 2007;Georgeton & Fougeron, 2014;Kuzla & Ernestus, 2011;Tabain, 2003a;Tabain & Perrier, 2005. These prosodic effects have also been studied in a variety of languages, including English, French, Korean, and Taiwanese (in addition to the papers already cited, see Keating et al, 2003).…”
Section: Articulatory Prosody and The Role Of Contrastmentioning
confidence: 99%
“…A related study drawing on corpora of German, Chinese, Russian, and Ukrainian poems showed that, for each language, the poem with the highest frequency of the plosives /p/, /b/, /t/, and /d/ was rated by native participants as joyful and high in activation whereas, again for each of these languages, the poem with the highest frequency of nasals (/m/, /n/) was evaluated as sad and low in activation (Auracher et al, 2010). These three studies suffer, however, from substantial limitations: they neither included the entire group of plosives (/p, b, t, d, k, g/, see, e.g., Wiese, 1996; Kohler, 1999; Kuzla and Ernestus, 2011) nor the entire class of nasals of the German language (/m, n, ŋ/; see, e.g., Wiese, 1996; Kohler, 1999). Specifically, they did not consider /k/ and /g/ in their analyses of the class of plosives, while /ŋ/ was disregarded regarding the class of nasals.…”
Section: Introductionmentioning
confidence: 99%